2017
DOI: 10.1002/adfm.201703576
|View full text |Cite
|
Sign up to set email alerts
|

Layered Simple Hydroxides Functionalized by Fluorene‐Phosphonic Acids: Synthesis, Interface Theoretical Insights, and Magnetoelectric Effect

Abstract: International audienceCopper- and cobalt-based layered simple hydroxides (LSH) are successfully functionalized by a series of fluorene mono- and diphosphonic acids, using anionic exchange reactions and a preintercalation strategy. The lateral functionalization of the fluorene moieties has only little impact on the overall structure of the obtained layered hybrid materials but it influences the organization of the molecules within the interlamellar spacing. For bulky fluorene (9,9-dioctyl derivative), luminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 111 publications
(190 reference statements)
0
34
0
Order By: Relevance
“…Then, the hydrolysis of phosphonate to phosphonic acid can be achieved in acidic condition . Note that we placed the bromine atom in meta position respective to the phosphonic acid on the benzene ring because we have previously observed that the use of rigid organic precursors that feature a low symmetry contributed to the formation of non‐centrosymetric hybrid materials . To this goal, we used an excess of 1,3 dibromobenzene as substrate to favor the monophosphonation to produce compound 1 ( Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the hydrolysis of phosphonate to phosphonic acid can be achieved in acidic condition . Note that we placed the bromine atom in meta position respective to the phosphonic acid on the benzene ring because we have previously observed that the use of rigid organic precursors that feature a low symmetry contributed to the formation of non‐centrosymetric hybrid materials . To this goal, we used an excess of 1,3 dibromobenzene as substrate to favor the monophosphonation to produce compound 1 ( Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Structures of MnPO 3 C 6 H 5 ⋅H 2 O and MnPO 3 C 6 H 4 ‐ m ‐Br⋅H 2 O: a) perovskite‐like MnPO 3 H 2 O layer containing PO 3 C tetrahedra, b) view of the MnPO 3 C 6 H 5 ⋅H 2 O structure along truea showing the b ≈ 14 Å periodicity after ref. , and c) view of the MnPO 3 C 6 H 4 ‐ m ‐Br⋅H 2 O structure along truea showing the c ≈ 31 Å periodicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 In a few cases, magneto-electric coupling was observed. [36][37][38] Since the properties of hybrid materials are influenced by the functionalization of organic precursors and after considering the incorporation of carboxylic acids 9 or halogen atoms into organic precursors 38,39 in addition to one or several phosphonic acid functions, 40 we investigate herein the conception of metal-phosphonate hybrids featuring phenol functions. Actually, only a few metal-phosphonate materials possessing phenol functions were previously reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Single-phase ME materials [3][4][5] are sparse in nature and have limited applications, since they show weak ME response at very low operating temperatures. [9,10] These ME heterostructures [11] enable the conversion between magnetic and electrical energies through mechanical coupling between magnetostrictive and piezoelectric phases, [12] allowing a large number of applications including magnetic sensors, actuators, switches, energy harvesters, inductors, and data storage devices for smart electronic applications. [9,10] These ME heterostructures [11] enable the conversion between magnetic and electrical energies through mechanical coupling between magnetostrictive and piezoelectric phases, [12] allowing a large number of applications including magnetic sensors, actuators, switches, energy harvesters, inductors, and data storage devices for smart electronic applications.…”
Section: Introductionmentioning
confidence: 99%